PENGETAHUAN REMAJA PUTRI TENTANG PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA SISWI DI SMA NEGERI 8 BANDA ACEH - Denni Hermartin; Shella Widya Gani (Jurnal Sains Riset, 2021)
Based on Hospital Information System (SIRS) in 2007 in Indonesia most cancer in hospitalized patient is breast cancer (16,85%). The high incidence of breast cancer is due to the lack of awareness of women to immediately check themselves if there is abnormalities in the breast. Breast cancer malignant patients mostly come when the stage is advanced, so the treatment can not be appropriate, therefore knowledge of breast self-examination itself is very important to detect early occurrence of abnormalities in the breast. The purpose of this research is to know the knowledge of young woman about SADARI in SMA Negeri 8 Banda Aceh. The type of this research is descriptive with cross sectional study design that is between variables with each other which is implemented on 8 s / d 13 May 2017. Respondent is 54 respondents obtained by random sampling by using questionnaires that have been designed. In general, the results showed that the knowledge of female teenagers about breast self-examination (SADARI) on female students in SMA Negeri 8 Banda Aceh Year 2017, is in the good category of 29 respondents (53.7%), knowledge of young women about the definition of breast self- SADARI) In School Students at SMA Negeri 8 Banda Aceh Year 2017, in the category of less that is 38 respondent (70,4%), knowledge of young woman about breast self examination purpose (SADARI) Student at SMA Negeri 8 Banda Aceh Year 2017, in the good category of 30 respondents (55.6%), the knowledge of young women about breast self-examination steps (SADARI) In the students in SMA Negeri 8 Banda Aceh Year 2017, in the good category of 33 respondents (53.7%) . Based on the results of the above research is expected to adolescents to always check their own breasts to be able to detect changes that occur in the breast.Keywords: Knowledge, BSE